[Afisz. Incipit] Wielka zabawa taneczna w "Cyganerii" ... (Gdańsk : [wydawca nieznany], 1949)
Afisz informujący o zabawie bez daty dziennej.
Keywords: Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.